Hubungan antara Peran Teman Sebaya dan Paparan Media Sosial dengan Tingkat Konsumsi Minuman Berpemanis pada Remaja: Association between the Role of Peers and Social Media Exposure with Level of Sugar-Sweetened Beverages Consumption in Adolescent - Fawziya, Vyanadia Rizka; Adi, Mateus Sakundarno; Wurjanto, Moh. Arie; Yuliawati, Sri (Amerta Nutrition, 2024)
Background: Sugar-sweetened beverages, favored by various groups, particularly adolescents, are associated with an increasing risk of obesity and diabetes mellitus. According to preliminary research conducted at SMAN 1 Serang, approximately 60% of students have a high level of sugar-sweetened beverages consumption. Role of peers and social media exposure is considered to have an association with level of sugar-sweetened beverage consumption in adolescents. Objectives: This research aimed to determine association between role of peers and social media exposure with level of sugar-sweetened beverages consumption in adolescents at SMAN 1 Serang. Methods: The analytic observational research was carried out using a cross-sectional design. The study population consisted of 1,085 students from classes X and XI, while the sample size comprised 300 students who were selected using stratified random sampling and the data obtained were analyzed with chi-square test. Independent variables were measured with a questionnaire consisting of 13 closed-ended questions, while the dependent variable was measured with a Food Frequency Questionnaire. Results: The majority of respondents had a high level of sugar-sweetened beverages consumption (54.3%), bad role of peers (55.7%), and exposure to social media (74.0%). Moreover, this research showed the association between the role of peers (p=0.0001) and social media exposure (p=0.037) with level of sugar-sweetened beverages consumption. Conclusions: This research showed a significant association between role of peers and social media exposure with level of sugar-sweetened beverages consumption in adolescents. Therefore, forming peer groups and using social media were expected to increase students' awareness, causing a substantial reduction in beverages consumption.